Cell adhesion induces overexpression of chromodomain helicase/ATPase DNA binding protein 1-like gene (CHD1L) and contributes to cell adhesion-mediated drug resistance (CAM-DR) in multiple myeloma cells. (August 2016) - Xu, Xiaohong; He, Yunhua; Miao, Xiaobing; Wu, Yaxun; Han, Jingling; Wang, Qiru; Liu, Jing; Zhong, Fei; Ou, Yangyu; Wang, Yuchan; He, Song
Highlights: The role of CHD1L was determined in MM for the first time. Cell adhesion increased the expression level of CHD1L in myeloma cells. CHD1L overexpression contributes to CAM-DR in MM cells. Abstract: Previous studies have shown that chromodomain helicase/ATPase DNA binding protein 1-like gene (CHD1L) exerts its anti-apoptotic function in many solid cancers. However, its role in human multiple myeloma (MM) has not been thoroughly elucidated. In this study, we investigate the role of CHD1L in MM. Preliminarily, up-regulation and down-regulation assay verified that CHD1L exerts its anti-apoptotic role through the apoptotic pathway involving caspase-9–caspase-3 apoptotic pathway in MM cells. In addition, we determined that CHD1L expression is increased when MM cells were adhered to fibronectin (FN) or bone marrow stromal cell line HS-5 cells and cell adhesion assay indicated that CHD1L siRNA reversed the high cell adhesion rate. Consistent with the reduced adhesion rate, the cells translated to a compromised cell adhesion-mediated drug resistance (CAM-DR) phenotype in MM. In summary, we will propose strategies for developing a CHD1L inhibitor for potential treatment of MM.